Epidemiology of Overuse Injuries in U.S. Secondary School Athletics from 2014-2015 to 2018-2019 Using the National Athletic Treatment, Injury, and Outcomes Network Surveillance Program. Issue 5 (31st May 2022) - Post, Eric G.; Simon, Janet E.; Robison, Hannah; Morris, Sarah N.; Bell, David R.
Background: Large-scale injury surveillance systems such as the National Athletic Treatment, Injury and Outcomes Network Surveillance Program (NATION-SP) allow for the investigation of injury rates in national samples of high school athletes. The most recent studies examining overuse injury rates in high school sports reported data from 2012-2013 and therefore may not reflect current overuse injury rates in high school sports. Hypothesis/Purpose: To 1) determine overuse time-loss (TL) and non-time-loss (NTL) injury rates among high school student athletes using NATION-SP data collected from 2014-2015 to 2018-2019 and 2) compare overuse injury rates based on student-athlete gender defined by sport, sport, and injury location. We hypothesized that TL overuse injury rates would be greater than those previously reported from earlier data (1.64/10, 000 athletic exposures (AEs) and 1.50/10, 000 AEs). We also hypothesized that overall overuse rates would be greater in girls' sports compared to boys' sports and would differ between injury types (TL vs. NTL) and injury location. Methods: During the 2014-2015 through 2018-2019 school years, NATION-SP documented TL and NTL injuries from 222 high schools. This study included 23 high school sports during preseason, regular season, and post-season competitions and practices. Overuse injuries were identified using a combination of reported injury mechanism and diagnosis. Injury counts, rates, and rate ratios (IRRs) were reported with 95% confidence intervals (CIs). Results: The overall overuse injury rate was 6.6/10, 000 AEs (95%CI=6.3, 6.9), the NTL overuse injury rate was 4.0/10, 000 AEs (95%CI=3.8, 4.3), and the TL overuse injury rate was 2.6/10, 000 AEs (95%CI=2.4, 2.8). The overuse injury rate was greater in girls' sports compared to boys' sports (IRR=1.8; 95%CI=1.6, 1.9). The highest rates of overuse injury regardless of sport gender were reported in girls' cross-country (20.0/10, 000 AEs; 95%CI=15.7, 25.1), girls' field hockey (17.6/10, 000 AEs; 95%CI=12.3, 24.5), and girls' track and field (17.5/10, 000 AEs; 95%CI=14.9, 20.4). Overuse injury rates were highest for the lower extremity compared to the upper extremity (IRR=5.45; 95%CI=4.76, 6.27) and for the lower extremity compared to the trunk and spine (IRR=11.08; 95%CI=9.21, 13.45). Conclusions: Using NATION-SP data collected over five consecutive school years, overuse injury rates among high school athletes were much greater than previously reported earlier in the decade. Awareness of overuse injury risk as well as prevention and intervention recommendations are necessary and should be specifically targeted towards cross-country, field hockey, and track and field athletes. Table 1. Total and Sport Gender Specific Overuse Injury Count and Athletic Exposures Figure 1. Overall and sport gender specific overuse injury rates across years of study data collection.